Ag-catalyzed InAs nanowires grown on transferable graphite flakes. (1st August 2016) - Meyer-Holdt, Jakob; Kanne, Thomas; Sestoft, Joachim E; Gejl, Aske; Zeng, Lunjie; Johnson, Erik; Olsson, Eva; Nygård, Jesper; Krogstrup, Peter
Abstract: Semiconducting nanowires grown by quasi-van-der-Waals epitaxy on graphite flakes are a new class of hybrid materials that hold promise for scalable nanostructured devices within opto-electronics. Here we report on high aspect ratio and stacking fault free Ag-seeded InAs nanowires grown on exfoliated graphite flakes by molecular beam epitaxy. Ag catalyzes the InAs nanowire growth selectively on the graphite flakes and not on the underlying InAs substrates. This allows for easy transfer of the flexible graphite flakes with as-grown nanowire ensembles to arbitrary substrates by a micro-needle manipulator. Besides the possibilities for fabricating novel nanostructure device designs, we show how this method is used to study the parasitic growth and bicrystal match between the graphite flake and the nanowires by transmission electron microscopy.